Supracondylar Humerus Fracture in Pediatrics - Ainun Fatiha Dea Putri; Ardhitio Musthafa Akmal; Athala Rania Insyira; Baiq Aliza Khansa Istika; I Gede Bramanty; I Gede Prabananda A; I Gusti Ayu Ratih C. N; Ni Komang Ayu T. Y; Rizqi Al Kasiron; Siska Julia Cindy W; Siti Jaisy Millah Hadaina (Research of Service Administration Health and Sains Healthys, 2025)
Supracondylar humerus fracture is the most common elbow fracture in children, particularly between the ages of 4 and 10 years. This injury typically occurs due to a fall on an outstretched hand, causing indirect trauma to the distal humerus, an area structurally thinner and more vulnerable to fracture. Clinical manifestations include pain, swelling, limited elbow motion, and, in severe cases, deformity or neurovascular impairment. Diagnosis is established through clinical assessment and radiographic evaluation, with key indicators such as the anterior humeral line and fat pad sign. Management is guided by the Gartland classification. Non-displaced fractures (Type I) are treated conservatively with immobilization, while displaced fractures (Types II, III, and IV) generally require closed reduction and percutaneous pinning to prevent complications such as neurovascular injury, compartment syndrome, malunion, and cubitus varus deformity. Early and appropriate treatment is essential to restore function and prevent long-term complications.